PROBIOTIC DAIRY PRODUCTS: PRODUCTION AND SENSORY EVALUATION - Chatterjee, Bandana; Modi, Kanchan; Patel, Tinkal (International Journal of Clinical and Biomedical Research, 2015)
Foods that affect specific functions or systems in the human body, providing health benefits beyond energy and nutrients, functional foods have experienced rapid market growth in recent years. This growth is stimulated by technological innovations and development of new products. The increasing Number of health-conscious consumers are interested in products that improve life quality. Since the global market of functional foods is increasing annually. Probiotics show considerable promise for the expansion of the dairy industry, especially in such specific sectors as yoghurts (Indian dahi), cheeses, beverages, ice creams, and other desserts. This article presents an overview of functional food and strategies for their development with some attention to probiotic dairy products. The special attention is paid to the sensory of such products to provide important information about the most desirable attributes. KEYWORDS: Functional foods; Dairy Products; Sensory properties; Probiotic strains.